(untitled) (Journal of Civil Engineering Researchers, 2023)
The moment frame is one of the most widely used seismic resistant systems in the world, due to its high formability and flexibility, this system causes a lot of displacement in the structure and force exceeding the capacity of the structural components. The bracing system is a suitable method to control the lateral displacement of the structure and the seismic improvement of the bending frame. The new type of bracing system that is used in the design of new systems and the improvement of old structures is non-buckling bracing, and in this research, their effect on the performance of 4, 7, and 10-story concrete moment frames under the Northridge, San Salvador, and Tabas earthquake has been investigated. The research method in this research is analytical-applied, which the results of this study showed; In the 4-story structure, the amount of wasted energy under the 3 considered earthquakes is equal to 0%, 0%, and 1% without buckling braces and 39%, 48% and 50% in the case with non-buckling braces and in the 7- story structure, the amount of energy consumed under the mentioned 3 earthquakes is equal to 0%, 0% and 0% without buckling braces and 40%, 45% and 51% in the case with non-buckling braces and also in the 10- story structure, the amount of energy consumed under the above 3 earthquakes is equal to 1%, 0% and 11% without buckling braces and 35%, 42% and 45% in the case with non-buckling braces. So, it was concluded that the performance of the structure in the case with non-buckling braces is better than in the case without non-buckling braces.